Potential benefits of postactivation potentiation protocols on tennis performance: A systematic review - Germic, A.; Filipcic, A.; Paravlic, A. (Strength and Conditioning Journal, 2024)
The study aimed to provide an overview of the benefits of postactivation potentiation (PAP) protocols on tennis performance. All procedures were in accordance with the PRISMA guidelines. After an online search, 8 studies with 133 tennis players were eligible for inclusion. Results showed that a variety of methods were used to elicit PAP in tennis players, with maximal voluntary isometric contraction showing promising results in improving serve velocity (SV) by 4.6 km·h-1 (3.4 ± 4.6%; ES = 0.711) immediately after the preconditioning activity (PCA). The most favorable effects of PAP on sprinting time and maximal power were observed in resistance training exercises using squats as PCA, with loads near 60% of 1 repetition maximum (1RM), whereas the heavy load leg press warm-up demonstrated positive effects on agility and power. By contrast, negative effects on SV were observed with heavy 600-g ball throws. Despite limitations in match application because of the post-activation performance enhancement effect duration, these protocols remain beneficial for training purposes. Calculating volume load relative to 1RM can provide helpful insights for optimal PAP. However, individualizing PAP protocols based on athletes' characteristics and training status seems crucial and should be investigated in future studies.